Regulation and Control: The Transformation of Agriculture in the Japanese Era, 1942-1945 - Rinda Handayani (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2025)
The Japanese presence in Indonesia (1942–1945) had a significant impact on various sectors, including the economy and agriculture. Japan implemented various policies and regulations to control the agricultural sector to meet their war needs in Java. This research aims to analyze the agricultural transformation introduced by Japan, especially in the aspects of regulation and control which include the introduction of new commodities, the application of cultivation techniques, and the formation of farmer organizations in the Java region. This research uses historical methods that include heuristics, criticism of sources (internal and external), interpretation, and historiography. The results show that although Japan's agricultural policy brings modernization through new cultivation techniques, on the other hand it also causes negative impacts, such as food scarcity and labor exploitation. Thus, the transformation of agriculture during the Japanese occupation had a complex influence on the agricultural sector in Indonesia.